2021
DOI: 10.1002/jts.22659
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Burnout and Secondary Traumatic Stress in Professionals and Volunteers Working With Forcibly Displaced People: A Systematic Review and Two Meta‐Analyses

Abstract: Research suggests that professionals and volunteers who work with forcibly displaced people (FDP) experience burnout and secondary traumatic stress (STS) as a result of working with such a highly traumatized population. In the present systematic review and meta‐analyses, we report the pooled prevalence rates of burnout and STS in individuals working both professionally and voluntarily with FDP. The CINAHL Complete, E‐Journals, ERIC, MEDLINE Complete, OpenDissertations, PsycARTICLES, and PsycINFO databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Like the findings reported by Denkinger and colleagues' ( 2018), these results revealed a significant correlation between interpreters' trauma history and STS symptom severity (Kindermann et al, 2017). Parallel with these findings, a recent meta-analysis of 15 studies demonstrated a pooled STS prevalence of 45% among professionals and volunteers working with forcibly displaced people (Roberts et al, 2021). Finally, Mishori and colleagues (2013) examined the prevalence of VTS among asylum evaluators (i.e., doctors and psychiatrists asked to document the evidence of torture and persecution) and found that 26.2% of the 192 participants reported having experienced vicarious trauma.…”
Section: Sts and Vts Among Refugee Service Providerssupporting
confidence: 82%
“…Like the findings reported by Denkinger and colleagues' ( 2018), these results revealed a significant correlation between interpreters' trauma history and STS symptom severity (Kindermann et al, 2017). Parallel with these findings, a recent meta-analysis of 15 studies demonstrated a pooled STS prevalence of 45% among professionals and volunteers working with forcibly displaced people (Roberts et al, 2021). Finally, Mishori and colleagues (2013) examined the prevalence of VTS among asylum evaluators (i.e., doctors and psychiatrists asked to document the evidence of torture and persecution) and found that 26.2% of the 192 participants reported having experienced vicarious trauma.…”
Section: Sts and Vts Among Refugee Service Providerssupporting
confidence: 82%
“…and Kjellenberg et al in which caregivers and professionals working with refugees and migrants reported high levels of CS and a lower risk for BO and CF suggesting their competence to manage the impact of work with trauma sufferers ( 9 , 17 ). Similarly, high levels of CS are reported in other studies ( 12 ). Apostolidou found that the positive emotions of professionals working with trauma sufferers were related to the gratitude they received from the sufferers and their improvement, as well as to the personal development resulting from that experience ( 18 ).…”
Section: Discussionsupporting
confidence: 87%
“…Overall, the impact of working with immigrants and refugees is well recognized by the existing literature. In a recent systematic review of the emotional consequences of trauma work for humanitarian professionals, eight studies focused on professional quality of life ( 12 ). However, only two of the studies included a small number of health professionals in their samples.…”
Section: Introductionmentioning
confidence: 99%
“…This study mainly focused on the associations between STS, EE and SS, especially whether the relation between STS and EE was mediated by SS. (Roberts et al, 2021), first responders (Greinacher et al, 2019), and soldiers (Cieslak et al, 2013;Penix, Kim, Wilk, & Adler, 2018). The current study focused on general mental healthcare providers, who worked in less risky conditions, which could explain the relative low prevalence of STS in our study.…”
Section: Discussionmentioning
confidence: 87%